2022
DOI: 10.3390/ma15124102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Color and Spectral Behavior of a Novel Flowable Resin Composite after Water Aging: An In Vitro Study

Abstract: Background: This study aimed to evaluate the color matching, light transmittance, and reflectance characteristics of the novel flowable resin composite OCF-001 (OCF). Methods: Fifty-four resin composite molds were made with simulated class I cavities of A2, A3, and A4 shades by filling the rubber mold interspace with Estelite Sigma Quick (ESQ), Gracefil Putty (GP) and Filtek Supremme Ultra (FSU). After applying the adhesive, three different flowable resin composites (n = 6), OCF, Gracefil LoFlo (GLF), and Supr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Resin composites are the most versatility demanded restorations for anterior and posterior teeth in dental practice due to their improved physical and mechanical properties as well as their satis ed aesthetic appeal through the developments in ller technology [2,3]. Since people's more concern for aesthetics, the research effort has focused on improving the matching the color of the resin composite to the surrounding cavity to increase their clinical service [4]. Composite technology rapidly evolves with new aesthetic characteristic of resin composites products being released in the market every year.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resin composites are the most versatility demanded restorations for anterior and posterior teeth in dental practice due to their improved physical and mechanical properties as well as their satis ed aesthetic appeal through the developments in ller technology [2,3]. Since people's more concern for aesthetics, the research effort has focused on improving the matching the color of the resin composite to the surrounding cavity to increase their clinical service [4]. Composite technology rapidly evolves with new aesthetic characteristic of resin composites products being released in the market every year.…”
Section: Introductionmentioning
confidence: 99%
“…Aesthetic resin composites with improved translucency and enhanced structural integrity provided better blending capabilities, which blended into the teeth even if the shade picked was a little off [5,6]. Shortly after the application of aesthetic resin composites, universal-shade resin composites are born on demand marketably, universal-shade is only single shade, which is expected to match nearly all shades of the surrounding tooth [4,7]. Some researches have reported that universal-shade type of resin composites revealed barely indistinguishable color difference compared to the conventional types of resin composites [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation